Pertumbuhan Mikroalga Botryococcus braunii Sebagai Penghasil Lipid Pada Medium Campuran Antara Air Kelapa Dan Air Laut - Bintoro Rudi Saputro; Endang Kusdiyantini; Hermin Pancasakti Kusumaningrum (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Energy needs in fuel sector tend to increase for supporting human life. Green microalgae (Chlorophyceae) can be used as an alternative solutions for bioenergy. Botryococcus braunii is lipid producer microalgae which can be processed further into biodiesel. Microalgae growth medium such as Walne can be subtituted with coconut water that reducing economical cost. This research aims to determine the growth of B. braunii using coconut water and its effect on lipid production. The experiment conducted into five treatments of coconut water consist of P0 (0%), P1 (10%), P2 (7.5%), P3 (5%), and P4 (2.5%) for five days incubation and three repetitive step. Microalgae growth was calculated according to cell count using haemocytometer. The results showed that 2.5% coconut water subtitution exhibited the best growth rate and lipid production, ie the amount of 547 cells / ml and produced lipid level according to these treatment increased 179% comparing with control. Keywords: Growth, Botryococcus braunii, Lipid, Coconut water, Seawater.